Genotipagem dos isolados de Giardia duodenalis de humanos e de cães na colônia de pescadores de Porto Said, Botucatu, São Paulo - David, Érica Boarato [UNESP] (2015)
Several species of protozoa cause acute or chronic gastroenteritis in humans, worldwide. The burden of disease is particularly high among children living in developing areas of the world, where transmission is favored by lower hygienic standards and scarce availability of safe water. However, asymptomatic infection and polyparasitism are also commonly observed in poor settings. Here, we investigated the prevalence of intestinal protozoa in two small fishermen villages, Porto Said (PS) and Santa Maria da Serra (SM), situated along the river Tietê in the State of São Paulo, Brazil. The villages lack basic public infrastructures and services, such as roads, public water supply, electricity and public health services. Multiple fecal samples were collected from 88 individuals in PS and from 38 individuals in SM, who were asymptomatic at the time of sampling and had no recent history of diarrheal disease. To gain insights into potential transmission routes, 49 dog fecal samples (38 from PS and 11 from SM) and 28 river water samples were also collected. All samples were tested by microscopy and PCR was used to genotype isolates of Giardia duodenalis, Blastocystis spp., Dientamoeba fragilis and Cryptosporidium spp. By molecular methods, the most common human parasite was Blastocystis spp. (prevalence, 45% in PS and 71% in SM), followed by D. fragilis (13.6% in PS, and 18.4% in SM) and G. duodenalis (18.2% in PS and 7.9% in SM); Cryptosporidium spp. were not detected. Further, G. duodenalis was found in 4 dogs (10.5%) in PS and 2 dogs (18.2%) in SM, whereas a single dog was found infected with Cryptosporidium canis. River water samples processed by filtration and immunomagnetic separation and examined by fluorescent microscopy, were negative for Cryptosporidium oocysts and Giardia cysts. Sequencing of the barcoding region of the small subunit ribosomal gene revealed large genetic variation among Blastocystis isolates, with subtypes (STs) that ...